Clustering of non-communicable disease risk factors among school teachers: A cross-sectional study in Kerala, India - Mini GK; Sangeeth KS; Anand Marthanda Pillai; Sarma PS; Thankappan KR (Clinical Epidemiology and Global Health)
Background: There is limited data on non-communicable disease (NCD) risk factors among teachers in low and middle-income settings. We assessed the prevalence and clustering of NCD risk factors among school teachers in Kerala. Methods: This study analyzed data from 2216 school teachers in the Thiruvananthapuram district of Kerala. The World Health Organization (WHO) STEPs questionnaire for NCD risk factor surveillance was used. We collected socio-demographic information and behavioural risk factors using STEP-1 and clinical measurements using STEP-2. We included WHO recommended four behavioural risk factors and four metabolic risk factors for analysis. Results: The main risk factors were physical inactivity (76.4 %) and overweight/obesity (68.8 %). Current tobacco use was reported by 5 % of men, while 13.4 % of men and 2.6 % of women reported alcohol use. A quarter of teachers consumed than five servings of fruits and vegetables daily. Self-reported diabetes prevalence was 10.6 % and dyslipidaemia was 22.4 %. Hypertension prevalence was 18.1 %. Only 2.8 % had no risk factors, 18.9 % had one, 37.7 % had two, and 40.6 % had three or more. Among physically inactive participants, the most common co-occurring risk factor was overweight, followed by insufficient fruit and vegetable intake. For overweight participants, physical inactivity and insufficient fruit and vegetable consumption were prevalent. In hypertensives, the most common co-morbidity was being overweight, followed by physical inactivity. Conclusion: A higher proportion of teachers had three or more NCD risk factors indicating the need for targeted interventions for school teachers to mitigate these risk factors to prevent NCDs.